Digitalizing Sharia-Based MSMEs in a Value-Oriented Islamic Economic System - Frida Yanti Sirait (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2026)
Sharia-based micro, small, and medium enterprises (MSMEs) are a vital pillar of Indonesia’s economy, contributing significantly to GDP and employment. Despite their strategic role, many of these enterprises face serious digitalization barriers that limit growth, market expansion, and transparent Sharia compliance. Traditional business models often fail to integrate Islamic ethical values with modern technology, creating an urgent need for a value-based digital transformation approach rooted in Islamic economic principles. This study examines the digitalization of Sharia-based MSMEs within a value-oriented Islamic economic framework, focusing on the role of financial technology innovations such as blockchain and digital platforms. Using a mixed-methods design, the research combines qualitative case studies of MSMEs across several provinces with quantitative analysis supported by interviews, surveys, and the Technology-Organization-Environment (TOE) framework integrated with Islamic value theory. The findings indicate that digital transformation significantly improves business performance when aligned with Islamic values. Digital adoption increases market reach, operational efficiency, and transparency of Sharia compliance. Blockchain technology strengthens halal certification verification, while digital payment systems enhance transaction efficiency. However, challenges persist, including low digital literacy, limited investment capital, regulatory uncertainty, and risks of value dilution. Overall, the study proves that technological innovation and Islamic values are compatible, offering a value-oriented digitalization model to support sustainable, ethical, and Sharia-compliant MSME development in Indonesia.